(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
The supremum for a set in a multi-dimensional, Dedikind complete topological space is defined. The example is given to illustrate that the condition of Dedilind complete is necessary for the existence of supremum.